RANCANG BANGUN RANTAI PASOK AGROINDUSTRI SORGHUM DI JAWA BARAT: KAJIAN LITERATUR DAN AGENDA RISET - Prasetyani, Rini; Marimin, Marimin; Arkeman, Yandra; Sugiarto, Sugiarto (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
Sorghum is a local food ingredient, and as it grows, it has the potential to reduce reliance on imported food. From the roots to the fruit, sorghum crops can be processed into a variety of food products, crafts, and medicines. Currently, sorghum flour is only available through imports. Supply Chain Analytics, Value Chain Management, Big Data, Supply Chain Performance, and Decision Support Systems are the five defined components of a sustainable supply chain. In the future, this research covered Decision Support Systems to Improve Unequal Profits Among Farmers, Supply Chain Management Strategies, and Supply Chain Performance to Increase Productivity. Several journals were collected by the author using the Publish or Perish 8 software, including Scopus 200 journals and databases Science Direct 145, and aside from that, there is knowledge of book literature as well as knowledge of other sciences. Then, using the VOS viewer software, look for novelty to see the novelty of previously unstudied relationships. This study's novelties include methodology and substance, such as: 1. production technology for managing the design and construction of a sustainable supply chain model for the agroindustry of sorghum; 2. Choosing sorghum and estimating demand for sorghum and sorghum products using technology in the supply chain. 3. Develop a partnership performance model for the sorghum cultivation business and identify sorghum production supplies in the supply chain. supply, 4. Create a distribution model and design a transportation network for sorghum products in the supply chain. Keywords: inventory forecasting, sorghum supply chain, transportation, PRISMA